Trends in information technology development in China - Qian, Weiqian; Havrys, Olha O. (Національний технічний університет "Харківський політехнічний інститут", 2024)
By analyzing technological innovation, policy support, industry application, and market dynamics, the current status and future direction of information systems development in China is assessed. The focus is on the application of technologies such as cloud computing, big data, artificial intelligence (AI) and the Internet of Things (IoT) in information systems, and how these technologies contribute to the digital transformation of the Chinese economy
Keywords: cloud computing; artificial intelligence; big data technology; blockchain; IoT